FEATURES OF THE CLINICAL COURSE OF CHRONIC RECURRENT APHTHOUS STOMATITIS - Mirvakhidova Nazokat.M, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation.  Chronic  recurrent  aphthous  stomatitis  is  one  of  the  most widespread  diseases  of  the  oral  mucosa.  The  prevalence  of  recurrent  aphthous stomatitis, according to various authors, ranges from 10 to 40% in different age groups of the population. Over the past 10 years, there has been a marked trend towards an increase  in  the  number  of  patients  with  recurrent  aphthous  stomatitis,  and  with  its severe  form.  Recurrent  aphthous  stomatitis  occurs  against  the  background  of sensitization of the body to conditionally pathogenic microorganisms of the oral cavity, viruses,  food  or  microbial  allergens.  Studies  have  shown  that  bacterial  allergies develop in patients with dysbiosis of the distal gastrointestinal tract.